Carl Beam: The Poetics of Being - Hill, Greg A. (National Gallery of Canada, 2010)
This major retrospective publication confirms Carl Beam (1943 - 2005) as one of North America's most important artists. Beam broke new ground throughout his career, notably as the first artist of Native Ancestry (Ojibwe) to have his work purchased by the National Gallery of Canada as Contemporary Art. Working in various mediums - photography, oil, acrylic, stone, cement, wood, ceramics and found objects - Beam's work continually explored the tensions between Western and Aboriginal relations. Featuring more than 50 of Beam's most remarkable works from his early career in the 1970s to the end of his production in the early 2000s, this richly illustrated monograph illuminates the artist's investigations into the metaphysical aspects of Western and Indigenous culture, while powerfully illustrating the wideranging physicality of his work. Source: Publisher
Section: 137 pages : illustrations (some color) ; 28 cm
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; _Nettoyé